2021
DOI: 10.1002/cssc.202101093
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Process to Construct Porous Ionic Polymers by Menshutkin Reaction

Abstract: The synthesis of porous ionic polymers (PIPs) via the Menshutkin reaction is intriguing because the reaction works smoothly in catalyst‐free condition with 100 % atom utilization. However, the rotation of methane site, nonrigid knots, and charge interaction all may cause collapses of the channel, which is detrimental to the synthesis PIP in solid‐state conditions. In this work, an inorganic salt (NaBr, NaCl: pollution‐free and easy to recycle) was rationally chosen as the hard template and effectively prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…We also explored the catalytic activity of Cu x Mo 1−x O y -H, Cu x Mo 1−x O y -C, and Cu x Mo 1−x O y -P in the reaction. The conversion rates of benzaldehyde are 37%, 67%, and 68%, respectively, which were lower than that observed for 42 Good stability is one of the important features of a solid catalyst. The recycling of Cu x Mo 1−x O y -M was tested under the optimized reaction conditions (entry 8, Table 1) by centrifugal separation.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We also explored the catalytic activity of Cu x Mo 1−x O y -H, Cu x Mo 1−x O y -C, and Cu x Mo 1−x O y -P in the reaction. The conversion rates of benzaldehyde are 37%, 67%, and 68%, respectively, which were lower than that observed for 42 Good stability is one of the important features of a solid catalyst. The recycling of Cu x Mo 1−x O y -M was tested under the optimized reaction conditions (entry 8, Table 1) by centrifugal separation.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…We also explored the catalytic activity of Cu x Mo 1– x O y -H, Cu x Mo 1– x O y -C, and Cu x Mo 1– x O y -P in the reaction. The conversion rates of benzaldehyde are 37%, 67%, and 68%, respectively, which were lower than that observed for Cu x Mo 1– x O y -M. It showed that the specific surface area of Cu x Mo 1– x O y was one of the key factors affecting activity …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Considering the fact that the double activation models of epoxides are believed to be widespread, indeed, a variety of metalloporphyrin-based PIPs can be constructed via the direct condensation strategy by using neutral metalloporphyrins and charged IL moieties as the building blocks, where the ionic sites are presented in the main chain of porphyrin backbones as described in Scheme . , However, there is evidence suggesting that the electrostatic interactions among charged groups tend to bring about poor reaction activity of ionic monomers or highly irregular stacking architecture that may decrease the surface areas, , thereby reducing the close contact of multiple catalytic sites and limiting mass transport in CO 2 -involved reactions . With the great achievements made recently, the development of high-surface-area metalloporphyrin-based PIPs having high-density catalytic active sites in the matched positions still remains a challenge owing to the lack of feasible synthetic strategies and the difficulty in the design and synthesis of functional porphyrin monomers and/or ionic building units. …”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, the renaissance of mechanochemistry is attributed to its inherent advantages such as eco‐friendliness and cost‐effectiveness. At present, mechanochemistry is widely used in various areas, such as metallurgy, mineral processing, construction, and syntheses of various organic, inorganic, and organic–inorganic hybrid nanomaterials [44–50] . Encouragingly, the facile strategy of mechanochemistry opens up new possibility for degradation of PET into valuable products or green synthesis of MOFs in a solvent‐free, room‐temperature, and short‐time manner.…”
Section: Introductionmentioning
confidence: 99%